Development of the Sea Fishery Supply Chain Performance Measurement System: A Case Study - Dzakiyah Widyaningrum; Nur Aini Masruroh (International Journal of Supply Chain Management, 2012)
Good performance measurement system is required to assess the success of supply chain. However, choosing the most appropriate indicator is not easy as it depends on the systems characteristics. Sea fishery industry characterized as perishable products, seasonal in production, and highly dependence on nature (uncontrollable). Motivated by the uniqueness of the sea fishery industry, this work proposed a performance measurement system for the sea fishery supply chain. The performance of the proposed model is evaluated using Indonesian sea fishery supply chain case, mostly consists of small and medium enterprises (SME). This instrument has six dimensions; efficiency, flexibility, responsiveness, product quality, process quality, facilities, and government involvement. Beside having specific indicators of sea fishery industry, the proposed instrument also considers the involvement of government. Further, this instrument can be used not only for monitoring but also suggesting directions for improvement.